Genetic polymorphism of merozoite surface protein-1 (MSP-1) block 2 allelic types in Plasmodium falciparum fi eld isolates from mountain and coastal area in West Sumatera, Indonesia (Faculty of Medicine Universitas Indonesia, 2011)
Background: The fi eld isolates of P. falciparum may display variant forms and different frequencies. This study was designed to know the diversity of allelic type of MSP-1 block 2 among P. falciparum isolates collected in a mountain and a coastal area in West Sumatera, Indonesia, and compare mountain and coastal area. Methods: A total of 56 P. falciparum infected blood samples, collected from 27 patients attending local health facilities in South Solok district in a mountain region and 29 patients attending a local health facilities in South Coastal district region, West Sumatera, Indonesia were used in this study. The regions flanking the highly polymorphic characters, block 2 for MSP-1, were genotyped by allele-specific nested-PCR to analyse the population diversity of parasite. Sequence analysis of the polymorphic regions of MSP-1 was also conducted to identify allelic diversity in the parasite population. Results: Diverse allelic polymorphism of MSP-1 was identified in P. falciparum isolates from a mountain area and a coastal area in West Sumatera, Indonesia, and most of the infections were determined to be mixed infections. Sequence analysis of MSP-1 block 2 revelaled that 16 different alleles for MSP-1 (3 for K1 type, 2 for MAD20 type and 2 for RO33 type) were identified. Conclusion: Extensive genetic polymorphism with diverse allele type was identified in MSP-1 in P. falciparum field isolates from a mountain and a coastal area. A high level of mixed infections was also obcserved, as was a high degree of multiplicity of infection. (Med J Indones 2011; 20:11-4) Keywords: allelic types, coastal area, mountain area, MSP-1 block 2, Plasmodium falciparum